Tanzania - Communicating Local Farming Knowledge - Mgumia, A.H. (World Bank, Washington, DC, 2012)
The link between the documentation of local knowledge and the dissemination of useful local technologies to farmers is generally weak in the indigenous technology development process. To fill gap, the Uluguru Mountains Agricultural Development Project (UMADEP) has been working with local farmers to document their local knowledge related to Natural Crop Protection (NCP) and to spread this knowledge to other farmers in the Uluguru Mountains using interesting and locally relevant education materials and farmer-led training workshops. The approach used by UMADEP involoves the local communities throughout the process of collection of the knowledge, documentation, and dissemination. In order to effectively communicate the message about NCP to communities UMADEP developed visual materials with simple instructions about the use of botanicals and with illustrations done in a comic book style. The production of posters adopted the following steps and approaches by: a) accessing the know-how of the innovation, b) defining communication needs; c) targeting the audience; d) visualization and production of artwork; e) field testing; and f) farmer-to-farmer dissemination.